2019
DOI: 10.1016/j.cub.2019.02.045
|View full text |Cite
|
Sign up to set email alerts
|

Aedes aegypti Mosquitoes Detect Acidic Volatiles Found in Human Odor Using the IR8a Pathway

Abstract: Graphical Abstract Highlights d Ae. aegypti Ir8a mutant mosquitoes cannot sense lactic acid, a human sweat component d Attraction to humans and human odor is reduced in Ir8a mutant mosquitoes d Ae. aegypti IR8a pathway responds to human-odor cues during blood feeding d The Ir8a mutant host-seeking defect cannot be rescued by other olfactory receptors SUMMARY Mosquitoes use olfaction as a primary means of detecting their hosts. Previously, the functional ablation of a family of Aedes aegypti olfactory receptors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
163
3
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(180 citation statements)
references
References 54 publications
6
163
3
3
Order By: Relevance
“…Due to increasing CO2 emission and exacerbated air pollution, humans and wild animals are more frequently exposed to acidic environments. Through affecting the olfactory system, acids disturb the ecosystem and interfere with the survival behaviors of wild animals by impeding their ability to sense predator or food odorants [1][2][3]. Recent studies have shown that acid-sensing in insects is mediated by IR8a and IR64a, two ionotropic receptors [2,17].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to increasing CO2 emission and exacerbated air pollution, humans and wild animals are more frequently exposed to acidic environments. Through affecting the olfactory system, acids disturb the ecosystem and interfere with the survival behaviors of wild animals by impeding their ability to sense predator or food odorants [1][2][3]. Recent studies have shown that acid-sensing in insects is mediated by IR8a and IR64a, two ionotropic receptors [2,17].…”
Section: Discussionmentioning
confidence: 99%
“…Through affecting the olfactory system, acids disturb the ecosystem and interfere with the survival behaviors of wild animals by impeding their ability to sense predator or food odorants [1][2][3]. Recent studies have shown that acid-sensing in insects is mediated by IR8a and IR64a, two ionotropic receptors [2,17]. Yet, it is unknown how acidic volatiles and protons activate OSNs of mammals and influence their olfactory communication.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To solve the growing problem of mosquito-borne disease, we need improved and more efficient gene editing methods. CRISPR/Cas9-based targeted disruption of genes in mosquito vectors of human pathogens is a powerful method to uncover underlying aspects of mosquito pathogen transmission biology that can be targeted for basic biological understanding and for mosquito control efforts [1][2][3][4][5] .…”
Section: Introductionmentioning
confidence: 99%
“…A recent study conducted on Ae. aegypti mosquitoes evidenced that IR8a pathway is required for sensing human-borne acidic volatiles (Raji et al, 2019). To a lesser extent, other skin VOCs such as 1-octen-3-ol, acetone and ammonia can also attract mosquitoes (Majeed et al, 2016;Raji and DeGennaro, 2017).…”
Section: Introductionmentioning
confidence: 99%